Drug-Induced Lupus with Leukocytoclastic Vasculitis Associated with Apixaban - Yang, John; Lena, Steffi; Tarditi, Daniel; Banker, Gopika (Case Reports in Rheumatology, 2021)
Drug-induced lupus is an iatrogenic-induced autoimmune disease with common offending agents well documented in the literature. To our knowledge, there are no prior case reports of drug-induced lupus associated with apixaban or any other direct oral anticoagulant. We describe a case of drug-induced lupus with leukocytoclastic vasculitis associated with apixaban started 15 days prior, after a WATCHMAN procedure for atrial fibrillation in an 86-year-old male previously anticoagulated on rivaroxaban.